1994
DOI: 10.1029/93tc01955
|View full text |Cite
|
Sign up to set email alerts
|

Postnappe stacking extension and exhumation of high‐pressure/low‐temperature rocks in the island of Crete, Greece

Abstract: The island of Crete consists largely of nappes of contrasting lithologies and metamorphism that were stacked southward during an Oligocene‐early Miocene N‐S compression, with the lower nappes undergoing a high‐pressure/low‐temperature (HP/LT) metamorphism. This was followed by a N‐S Miocene crustal extension that caused thinning of the nappes and uplift of the HP/LT metamorphic rocks. Ductile conditions took place in the lower nappes associated with a retrograde greenschist metamorphism, while semiductile to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
128
0
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 35 publications
(2 reference statements)
0
128
0
8
Order By: Relevance
“…Vertical axis block rotations in the west Aegean region (50°since ∼15 Ma [van Hinsbergen et al, 2005b]) are well established, but have been shown to postdate most of the back-arc extension history , illustrating that the block rotation history of the Aegean is perhaps partly accommodated by, but not directly caused (if at all) by, back-arc extension. Moreover, most of the rotating region lies to the northwest of the Cycladic and south Aegean crystalline complexes where much of the Aegean extension was accommodated [Gautier et al, 1993;Fassoulas et al, 1994;Gautier and Brun, 1994;Jolivet et al, 1994bJolivet et al, , 1996Ring et al, 2003b;Jolivet and Brun, 2010]. Although relations between rotation and exhumation in the Rhodope core complex have been postulated [Brun and Sokoutis, 2007;van Hinsbergen et al, 2008a], the region that could have experienced major extension-related rotations in the west lies offshore central or southwestern Greece (Figure 1).…”
Section: Hinsbergen Et Al: Exhumation With a Twistmentioning
confidence: 99%
“…Vertical axis block rotations in the west Aegean region (50°since ∼15 Ma [van Hinsbergen et al, 2005b]) are well established, but have been shown to postdate most of the back-arc extension history , illustrating that the block rotation history of the Aegean is perhaps partly accommodated by, but not directly caused (if at all) by, back-arc extension. Moreover, most of the rotating region lies to the northwest of the Cycladic and south Aegean crystalline complexes where much of the Aegean extension was accommodated [Gautier et al, 1993;Fassoulas et al, 1994;Gautier and Brun, 1994;Jolivet et al, 1994bJolivet et al, , 1996Ring et al, 2003b;Jolivet and Brun, 2010]. Although relations between rotation and exhumation in the Rhodope core complex have been postulated [Brun and Sokoutis, 2007;van Hinsbergen et al, 2008a], the region that could have experienced major extension-related rotations in the west lies offshore central or southwestern Greece (Figure 1).…”
Section: Hinsbergen Et Al: Exhumation With a Twistmentioning
confidence: 99%
“…Fassoulas et al, 1994;Jolivet et al, 1996) to explain the removal of overburden from above the PQ unit. However, the applicability of this mechanism remains highly questionable since either OligoceneEarly Miocene extensional related basins or normal-sense metamorphic breaks within the PQ unit have been not reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…In Crete, the shape of strain ellipsoid varies from flattening via plane to prolate (Fassoulas et al, 1994;Zulauf et al, 2002). 3D strain data from north Peloponnese show slightly constrictional to plane strain conditions, with k being approximately 1.4 .…”
Section: Finite Strainmentioning
confidence: 99%
See 2 more Smart Citations